1.3.3 Extending eFFBD formalism to task model. Issue 1 (July 2014) - Prun, Daniel
Abstract In this paper, we study how eFFBD formalism can be modified to encompass task modeling. eFFBD is a formalism widely used by System Engineering community to model complex systems through a functional point of view. Task models are used by Human Factor community to express and analyze human activities. Although they appear to be complementary, functional modeling and task modeling are rarely used jointly. This separation contributes to reinforce barriers between disciplines and leads to inefficient system engineering processes. In order to improve this situation, we decided to extend eFFBD formalism to encompass task model expressivity. Based on eFFBD and task models comparison, we identify the need to add 3 new operators to eFFBD: suspend, resume and disable. Then we propose definition of a syntax and a formal semantic for these new operators. Our proposal is illustrated through the presentation of LEXE: an experimental tool supporting modeling and simulation of eFFBD, and its application on a concrete case.